LASER SHOCK EXPERIMENTS WITH NANOSECONDS PULSES: A NEW TOOL FOR THE REPRODUCTION OF SHOCK DEFECTS IN OLIVINE - Langenhorst F.; Boustie M.; Migault A.; Romain J.P. (My University, 1999)
Laser shock experiments with olivine have been carried out in order to test the capability of this new experimental approach to produce known shock defects in olivine. To determine the shock conditions, numerical simulations of experiments have been undertaken, indicating the generation of a rapidly decaying shock wave with an initial pressure of 60 GPa and a duration of 5 ns. The pressure prevailed thus distinctly shorter than in conventional shock experiments with explosives or light gas guns (0.1-1 μs). Despite this shorter pressure pulse in our laser experiment, TEM revealed that a high density of dislocations and planar fractures was activated in olivine up to a depth of 30 μm. A drastic decrease of dislocation and fracture densities observed deeper in the sample is attributed to the decay of the shock wave. The dislocation systems and the orientations of planar fractures in our experiment are identical to those found in naturally shocked olivine. The TEM observations indicate furthermore that fractures in olivine are the sources of dislocations and that the stress field around fractures determines which slip system is activated. Our study demonstrates that laser shock experiments are not only a powerful new tool in the reproduction of shock defects but also an indispensable tool to understand better the role of time in impact processes and the formation mechanisms of shock defects.
Keywords: LASER METHODS; SHOCK METAMORPHISM; PLANAR DEFORMATION FEATURES; OLIVINE